Implementasi Load Balancing Web Server Dengan Algoritme Weighted Least Connection Pada Software Defined Network - Hafizhul Karim; Rakhmadhany Primananda; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The problem of the web server is many of requests used by the user so that the workload on the server increases quickly resulting in the server down. Loadgbalancing is a techniqueato distribute incoming traffic between available serversaso that requestsxcan beahandled and respond faster. This research uses weighted least connection algorithm. The weighted least connection algorithm divides the server load based on the weight value. Software Defined Network Architecture (SDN) is programmable and provides facilities to the Network Administrator to design and implement load balancing strategies without vendor limitations. For implementation use mininet and controller used with POX. Parameters used for testing are connection rate, throughput, and CPU usage. The tool used for testing is httperf. The result of connection rate and throughput testing by giving client request 3000 with the rate of 75, 150, and 300 with the highest connection rate is 296,28 Conn/s, the lowest response time is 2,34 ms and the highest throughput value is 805,66 KB/s. And the last result of testing CPU usage, server 1 has a value of 21.6%, server 2 has a value of 24.6%, and server 3 has a value of 26.3%.